An anxious relationship between Autism Spectrum Disorder and Gut Microbiota: A tangled chemistry?. (May 2022) - Vellingiri, Balachandar; Aishwarya, S.Y.; Benita Jancy, S.; Sriram Abhishek, G.; winster Suresh babu, Harysh; Vijayakumar, Padmavathi; Narayanasamy, Arul; Mariappan, Sujitha; Sangeetha, R.; Valsala Gopalakrishnan, Abilash; Parthasarathi, Ramakrishnan; Iyer, Mahalaxmi
Highlights: ASD is a multifactorial neurodevelopmental disorder. The gut microbiota is significant in the formation and onset of ASD. Gut and brain have a bi-directional communication. This review discusses about gut microbiota, its metabolites and its role in ASD. Abstract: Autism spectrum disorder (ASD) is a serious multifactorial neurodevelopmental disorder often accompanied by strained social communication, repetitive behaviour, immune dysregulation, and gastrointestinal (GI) issues. Recent studies have recorded a link between dysbiosis in the gut microbiota (gm) and the primary stages of ASD. A bidirectional connection (also called microbiota-gut-brain-axis) exchanges information between the gut bacteria and central nervous system. When the homeostasis of the microenvironment of the gut is dysregulated, it causes oxidative stress, affecting neuronal cells and neurotransmitters, thereby causing neurodevelopmental disorders. Studies have confirmed a difference in the constitution of gut bacteria among ASD cases and their controls. Numerous studies on animal models of ASD have shown altered gm and its association with abnormal metabolite profile and altered behaviour phenotype. This process happens due to an abnormal metabolite production in gm, leading to changes in the immune system, especially in ASD. Hence, this review aims to question the current knowledge on gm dysbiosis and its related GI discomforts and ASD behavioural symptoms and shed light on the possible therapeutic approaches available to deal with this situation. Thereby, though it is understood that more research might be needed to prove an association or causal relationship between gm and ASD, therapy with the microbiome may also be considered as an effective strategy to combat this issue.